Parmalim and Contemporary Hegemony of the World Religion's Missionary Agenda in Aceh Singkil - Pohan, Zulfikar Riza Hariz (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
As a local religion, Parmalim in Aceh Singkil Regency Aceh Province is currently experiencing marginalisation in the presence of world religions such as Islam, Catholicism, and Protestantism. Based on the perspective of Islamic puritanism and Christian missionaries, Parmalim is categorised as unreligious or heretical. This study aims to analyse the genealogies of distribution and changes in Parmalim as the religious identity that has spread in Aceh Singkil. This qualitative research obtains the data through observation, interview, and documentation for two months. This study found that a segment of the Singkel community adheres to Parmalim as their cultural identity. Religious leaders, such as clerics and priests, actively seek to convert Parmalim adherents to Islam or Christianity through da’wah and missionary agenda. The hegemony of both Islam and Christianity makes their right still restricted. Thus, this study suggested the stakeholders fulfill their rights in education and religious and cultural practices as their basic needs.